LIKE SEX4 1 Acts as a β-Amylase-Binding Scaffold on Starch Granules during Starch Degradation. Issue 9 (2nd July 2019) - Schreier, Tina B.; Umhang, Martin; Lee, Sang-Kyu; Lue, Wei-Ling; Shen, Zhouxin; Silver, Dylan; Graf, Alexander; Müller, Antonia; Eicke, Simona; Stadler-Waibel, Martha; Seung, David; Bischof, Sylvain; et al.
Abstract : The glucan phosphatase family member LIKE SEX4 1 does not act as a phosphatase during starch degradation, instead functioning as a protein scaffold on the starch granule surface to bind β-amylases. Abstract: In Arabidopsis ( Arabidopsis thaliana ) leaves, starch is synthesized during the day and degraded at night to fuel growth and metabolism. Starch is degraded primarily by β-amylases, liberating maltose, but this activity is preceded by glucan phosphorylation and is accompanied by dephosphorylation. A glucan phosphatase family member, LIKE SEX4 1 (LSF1), binds starch and is required for normal starch degradation, but its exact role is unclear. Here, we show that LSF1 does not dephosphorylate glucans. The recombinant dual specificity phosphatase (DSP) domain of LSF1 had no detectable phosphatase activity. Furthermore, a variant of LSF1 mutated in the catalytic cysteine of the DSP domain complemented the starch-excess phenotype of the lsf1 mutant. By contrast, a variant of LSF1 with mutations in the carbohydrate binding module did not complement lsf1 . Thus, glucan binding, but not phosphatase activity, is required for the function of LSF1 in starch degradation. LSF1 interacts with the β-amylases BAM1 and BAM3, and the BAM1-LSF1 complex shows amylolytic but not glucan phosphatase activity. Nighttime maltose levels are reduced in lsf1, and genetic analysis indicated that the starch-excess phenotype of lsf1 is dependent on bam1 and bam3 . We propose that LSF1 binds β-amylases at the starch granule surface, thereby promoting starch degradation.